Case Report: Progressive Asymmetric Parkinsonism Secondary to CADASIL Without Dementia - Guo, Weihang; Xu, Baolei; Sun, Hong; Ma, Jinghong; Mei, ShanShan; Zeng, Jingrong; Sun, Junyan; Xu, Erhe (Frontiers in Neurology, 2022)
Parkinsonism is a rare phenotype of cerebral autosomal dominant arteriopathy with subcortical infarction and leukoencephalopathy (CADASIL), all of which involve cognitive decline. Normal cognition has not been reported in previous disease studies. Here we report the case of a 60-year-old female patient with a two-year history of progressive asymmetric parkinsonism. On examination, she showed severe parkinsonism featuring bradykinesia and axial and limb rigidity with preserved cognition. Magnetic resonance imaging (MRI) revealed white matter hyperintensity in the external capsule and periventricular region. Dopaminergic response was limited. A missense mutation c.1630C>T (p.R544C) on the NOTCH3 gene was identified on whole-exome sequencing, which confirmed the diagnosis of vascular parkinsonism secondary to CADASIL. A diagnosis of CADASIL should be considered in asymmetric parkinsonism without dementia. Characteristic MRI findings support the diagnosis.